2018
DOI: 10.1111/1462-2920.14265
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting prevalence of selection and drift in the community structuring of bacteria and microbial eukaryotes

Abstract: Whether or not communities of microbial eukaryotes are structured in the same way as bacteria is a general and poorly explored question in ecology. Here, we investigated this question in a set of planktonic lake microbiotas in Eastern Antarctica that represent a natural community ecology experiment. Most of the analysed lakes emerged from the sea during the last 6000 years, giving rise to waterbodies that originally contained marine microbiotas and that subsequently evolved into habitats ranging from freshwate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
142
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(163 citation statements)
references
References 48 publications
(87 reference statements)
20
142
1
Order By: Relevance
“…Stegen et al () proposed a null modelling approach (requiring phylogenetic signal in species niche) that could better infer the relative influence of ecological processes on microbial community assembly. So far, using this approach, several studies have quantified and compared the processes that govern the biogeographic patterns of bacteria and microeukaryotes in marine and/or lake waters (Logares et al, ; Wu et al, ). However, the relative importance of major processes in governing biogeography of total archaeal community or major archaeal groups across coastal waters is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Stegen et al () proposed a null modelling approach (requiring phylogenetic signal in species niche) that could better infer the relative influence of ecological processes on microbial community assembly. So far, using this approach, several studies have quantified and compared the processes that govern the biogeographic patterns of bacteria and microeukaryotes in marine and/or lake waters (Logares et al, ; Wu et al, ). However, the relative importance of major processes in governing biogeography of total archaeal community or major archaeal groups across coastal waters is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…These values are lower to those found in prokaryotic communities (i.e., 40% in El‐Swais, Dunn, Bielawski, Li, & Walsh, ). A possible explanation is that environmental selection has a different importance in microbial eukaryotic and prokaryotic plankton (Logares et al, ). But also, biotic factors not considered here, such as prey abundance or viral and predatory mortality, could be explaining changes in community composition.…”
Section: Discussionmentioning
confidence: 99%
“…This conceptual framework, which derives mostly from the study of plants and animals, has recently been applied to the microbial world (Hanson, Fuhrman, Horner‐Devine, & Martiny, ; Logares et al, ; Nemergut et al, ; Stegen et al, ). In prokaryotes, the analysis of community turnover along multiple spatial gradients indicates that environmental selection seems to be the most important process structuring communities (Hanson et al, ; Lindström & Langenheder, ), although there is also evidence that stochastic processes (e.g., drift and dispersal) have a role (Logares et al, ; Ofiteru et al, ). In the last years, several studies have also analysed the temporal turnover of microbial communities (Bunse & Pinhassi, ; Fuhrman, Cram, & Needham, ).…”
Section: Introductionmentioning
confidence: 99%
“…This modest role of selection in structuring the tropical and subtropical sunlit-ocean microbiome is consistent with the weak environmental gradients characterizing this habitat. In other habitats featuring a high selective pressure, such as Antarctic waterbodies that display a strong salinity gradient, the role of selection in structuring bacteria has been reported to be much higher, accounting for up to ~70% of the community turnover (49). The measured relative importance of selection is also a consequence of the global scale of our survey.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also found a higher importance of drift in determining the community structure of bacteria when compared with phytoplankton populating freshwater and brackish habitats (79). In contrast, drift was the prevalent community-structuring mechanism in unicellular eukaryotes populating lakes in a relatively small geographic area that features a strong salinity gradient, having a low importance for the structuring of prokaryotic communities (49). Likely, the relative importance of drift in structuring prokaryotes or unicellular eukaryotes is dependent on the selective strength of specific habitats, the occurrence of adaptive processes (49) or barriers to dispersal.…”
Section: Discussionmentioning
confidence: 99%